2010
DOI: 10.5487/tr.2010.26.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trichlorfon Pesticide Residues in Milk via Gas Chromatography with μ-Electron Capture Detection and GC-MS

Abstract: The pesticide trichlorfon is readily degraded under experimental conditions to dichlorvos. A method has therefore been developed by which residues of trichlorfon in milk are determined as dichlorvos, using gas chromatography with μ-electron capture detection. The identification of dichlorvos was confirmed by mass spectrometry. Milk was extracted with acetonitrile followed by centrifugation, freezing lipid filtration, and partitioning into dichloromethane. The residue after partitioning of dichloromethane was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, a fast and sensitive detection of pesticide residues in food has become increasingly important. Traditional analytical methods, such as gas chromatography 6,7 or high-performance liquid chromatography, 8,9 oen coupled with mass-selective detectors, are signicantly timeconsuming and expensive. These methods are still performed in laboratory, but they are not suitable for fast eld detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a fast and sensitive detection of pesticide residues in food has become increasingly important. Traditional analytical methods, such as gas chromatography 6,7 or high-performance liquid chromatography, 8,9 oen coupled with mass-selective detectors, are signicantly timeconsuming and expensive. These methods are still performed in laboratory, but they are not suitable for fast eld detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, food safety control is a public issue which cannot be restricted by a laboratory environment and trained technicians. These GS-MS, HPLC, and other similar methods require sophisticated apparatuses and complex chemical pretreatment [34,35]. The proposed method retains the advantages of being straightforward in operation, inexpensive, and readily accessible in materials just like the rapid pesticide test strips based on enzyme inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…10 À3 mg L À1 ), a signicantly lower LOD in comparison with other techniques. 14,[47][48][49] It was therefore concluded that the prepared electrochemical sensor exhibits remarkable advantages with a high sensitivity, wide linear range and low LOD.…”
Section: Electrochemical Detection Of Melamine and Trichlorfonmentioning
confidence: 99%